Muslim Identity of Indonesian Public Figures on Social Media during Eid al-Fitr - Aulia Putri Meidina (Jogjakarta Communication Conference (JCC), 2026)
This study aims to explain how Muslim identity is constructed through Instagram content by Indonesian public figures, specifically within the context of the 1447 H Eid al-Fitr celebration. Employing a qualitative approach rooted in the constructivist paradigm, the study views meaning as the product of interpreting cultural symbols. Roland Barthes' semiotic model is used to analyze signs, symbols, and visual elements across three levels of meaning: denotation, connotation, and myth. The study focuses on three Indonesian Muslim public figures Husein Ja'far Al Hadar, Oki Setiana Dewi, and Zaskia Adya Mecca selected for their high visibility, active social media presence, and consistent representation of Islamic values. These findings reveal that Muslim identity during Eid al-Fitr is expressed through visuals that highlight spirituality, modesty, and togetherness. The content shapes an "ideal Muslim" archety pereligious, reflective, and digitally active with the three public figures presenting diverse yet consistent models of identity.